The dust of just beginning - Don Kerr (Mingling Voices, 2010)
Don Kerr knows prairie culture better than most-he knows it from the inside out. He has made us aware of ourselves through his numerous volumes of poetry, his fiction, his many plays, his histories, and his interest in heritage. In this mature, accomplished collection, we can once again admire his unique prairie voice-minimalist, self-effacing, direct yet subtle and nuanced, immersed in his love of the vernacular language of this place. His line is muscular, his timing impeccable, his broad strokes with so few words exemplary.